Breaking Barriers: Unraveling the Challenges Hindering AI Adoption in Marketing Across Different Industries in the United States - Renganathan, Deepak (Digital Repository of Theses - SSBM Geneva, 2024)
In today's world, artificial intelligence is utilized across various industries to replicate human intelligence traits such as learning, problem-solving, and planning. In marketing, AI is key in aiding decision-making processes and involving customers more personally. The range of AI technologies applicable to marketing is extensive and can be categorized as machine learning algorithms, natural language processing (NLP), and recommendation engines. These technologies enable the collection, analysis, and prediction of consumer behaviour on unprecedented accuracy and scale, allowing for targeted and customized content. This study aims to explore how AI can be effectively employed in different aspects of the marketing landscape and evaluate the extent of its adoption and potential barriers in various industries in the United States. The study employed mixed methods, including surveys and interviews with CMOs and AI thought leaders. The online survey had 100 participants of both genders, while 10-15 semi-structured interviews were conducted. Survey data was analysed using quantitative analysis with SPSS, and open-ended questions were analysed through thematic analysis. The study highlighted the status of AI implementation in marketing and identified factors likely to impact organizations' ability to leverage the value of AI. Key emerging issues include data integration, a need for more skilled personnel, and work culture, commonly encountered during AI implementation in digital transformation. "Content Generation" emerged as the marketing area where firms anticipate AI to have the greatest influence in the next year, according to more than one-third of the survey respondents. There is also concern about potential job loss due to AI, with 23.6% of the workforce expressing worry about the future of their employment. Overcoming the barriers will require honest discussions about how AI can enhance, rather than replace, human abilities. Presently, more than 80% of the companies are NOT driving AI as an Agenda. They are on Wait and Watch and are apprehensive due to barriers on the path. The study concluded that AI tools can be used across organizations to improve client experiences and overall marketing outcomes, providing companies with a competitive edge in the market. By prioritizing internal opportunities and addressing ethical concerns, companies can leverage the positive effects of implementing AI systems to achieve organizational goals. However the path is not easily achievable and needs a rigorous change management agenda